Musical Shevchenkiana of Yevhen Stankovych: Interpretation of the Poetical Word in the Oratory “Taras Passions” - Vasylenko, Olha (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the article is to consider a new perspective of genre transformation in the Ukrainian oratorio of the 21st century, studied in the aspect of the relationship between poetic text and music. The work of Yevhen Stankovуch seems to be the pinnacle of the evolution of passions, during which textual interpolations changed and creatively renewed the genre canon. Despite the significant cultural and social resonance of the oratorio Taras Passion, its creative discoveries have not found coverage in scientific discourse yet. Main objectives of the study are to investigate the methods of conceptualizing the poetic word of Taras Shevchenko in the musical language of Y. Stankovуch’s oratorio and to reveal the genre innovations of the work. Such perspectives of analysis outline the boundaries of the novelty of this article. The research methodology is based on the methods of historical, cultural, phenomenological analysis. Their involvement is justified by the complex nature of the scientific problems of the article. Historical method reveals the general content and artistic specificity of the selected segment of Ukrainian musical history; culturological method focuses research on the different types of genres literary, artistic and musical culture; phenomenological method provides the study of certain conceptual contours and promotes the semantic differentiation involved in the analysis of multilevel cultural and artistic phenomena. Results and conclusions. The features of the uniqueness of modern oratorio opuses with the title “Passion” are determined. The ways of conceptualizing the poetic word in the choral music by Yevhen Stankovych are revealed: they are determined by the process that is able to combine various elements of Ukrainian ethnic culture as well as spiritual and religious traditions. The figurative and ideological concepts of word and music are subordinated to the main principles of the Ukrainian mentality (cordocentrism (philosophy of the heart), sacrifice and chivalry). The multidimensionality of the semantic field of Taras Shevchenko’s poetry is noted, as a result of which the real characters of the national liberation history are endowed with an aura of holiness like biblical persons. The gallery of various images of Y. Stankovych’s oratorio synthesizes the peculiarities of the national worldview and the evangelical virtues. In the pantheon of images of holy martyrs, sung in music, the composer places the image of T. Shevchenko. It is indicated that the story of the last days of the earthly life of the St. Virgin, the Prophet, Jan Hus is of particular importance. The principles of selecting fragments of T. Shevchenko’s poems for the libretto of the oratorio directly correspond to the genre canons of passions. The author defines the peculiarities of the composer’s interpretation of the personality of T. Shevchenko the poet as a prophet, patriot, bearer of the sacred Word, an ardent preacher of the ideas of spirituality, a bright exponent of the ethical position and spiritual tradition of the ethnos. At the same time, he acts as the narrator of the oratorio. The prerequisites for the transformation of the genre structure of the work of Y. Stankovych in the context of inheritance of the methods of text interpolation, up to their radical rethinking, are considered. The correspondence of the compositional and structural norms of sacred utterance in the poetry of T. Shevchenko and in the music of Y. Stankovych has been proved. It is indicated that the text genres of prayer, biblical epigraphs, retellings of passionate subjects, Church Slavonic archaic vocabulary of verses are revealed by the composer in the corresponding musical genres (znamenny chant, chorale, hymn, bellringing) and in the parameters of the expressive style. It is indicated that the drama of T. Shevchenko’s poetic style directly corresponds to the immanent qualities of a composer-symphonist and is realized by the orchestral parameter.